Coupled sulfur, iron and molybdenum isotope data from black shales of the Teplá-Barrandian unit argue against deep ocean oxygenation during the Ediacaran. (15th December 2015) - Kurzweil, Florian; Drost, Kerstin; Pašava, Jan; Wille, Martin; Taubald, Heinrich; Schoeckle, Daniel; Schoenberg, Ronny
Abstract: The Earth's atmosphere and hydrosphere changed from an Archean anoxic to a modern oxygenated world in two major steps, the Paleoproterozoic Great Oxidation Event (2.4–2.3 billion years ago) and the Neoproterozoic Oxidation Event (0.8–0.5 billion years ago). Both events had a strong influence on the availability of redox sensitive and bio-essential metals within the ocean and are, thus, strongly linked to fundamental biological innovations and diversification. Biological diversification during the Precambrian–Cambrian transition between 555 and 540 million years ago may have been driven by ocean–atmosphere oxygenation. The exact timing and the extent of (deep) ocean oxygenation within this time period remains unresolved though. Here we present major and trace element compositions as well as Mo, S and Fe isotopic data of organic-rich black shales from the Teplá-Barrandian unit, Czech Republic. New in situ zircon U–Pb ages provide a maximum depositional age of 559.8 ± 3.8 million years. Black shales with strong metal enrichment show low δ 56 Fe values due to the dominance of authigenic pyrite-Fe with δ 56 Fe values around −0.6‰ over detrital Fe with δ 56 Fe values around 0.1‰. Samples with lower authigenic metal enrichment show relatively low Mo/TOC ratios and increasing δ 34 S values, which is interpreted to reflect basinal restriction and longer seawater renewal times. In analogy to the modern Black Sea, the accompanied depletion of basinal Moaq due to near quantitative Mo removal might have led to the preservation of the seawater δ 98 Mo in the respective black shales. Our best estimate for this seawater Mo isotopic composition <560 million years ago is +1.2‰ in δ 98 Mo, which is nearly identical to seawater δ 98 Mo values inferred from Mid-Proterozoic black shales. The lack of higher δ 98 Mo values in black shales (and seawater) argues against contemporaneous Mn oxide formation in well oxygenated deep sea settings, which would preferentially adsorb isotopically light Mo leaving behind an isotopically heavy ocean. By contrast, the deep ocean might have remained ferruginous with the hydrothermal Fe still outbalancing surficial oxygen production. Our results therefore contribute to a growing data set, which suggests limited deep water oxygenation during major biological innovations in the late Ediacaran period.